Sulfide enrichment along igneous layer boundaries in the lower oceanic crust: IODP Hole U1473A, Atlantis Bank, Southwest Indian Ridge. (1st March 2022) - Pieterek, Bartosz; Ciazela, Jakub; Boulanger, Marine; Lazarov, Marina; Wegorzewski, Anna V.; Pańczyk, Magdalena; Strauss, Harald; Dick, Henry J.B.; Muszyński, Andrzej; Koepke, Juergen; Kuhn, Thomas; Czupyt, Zbigniew; et al.
Abstract: Reactive porous or focused melt flows are common in crystal mushes of mid-ocean ridge magma reservoirs. Although they exert significant control on mid-ocean ridge magmatic differentiation, their role in metal transport between the mantle and the ocean floor remains poorly constrained. Here we aim to improve such knowledge for oceanic crust formed at slow-spreading centers (approximately half of present-day oceanic crust), by focusing on specific igneous features where sulfides are concentrated. International Ocean Discovery Program (IODP) Expedition 360 drilled Hole U1473A 789 m into the lower crust of the Atlantis Bank oceanic core complex, located at the Southwest Indian Ridge. Coarse-grained (5–30 mm) olivine gabbro prevailed throughout the hole, ranging locally from fine- (<1 mm), to very coarse-grained (>30 mm). We studied three distinct intervals of igneous grain size layering at 109.5–110.8, 158.0–158.3, and 593.0–594.4 meters below seafloor to understand the distribution of sulfides. We found that the layer boundaries between the fine- and coarse-grained gabbro were enriched in sulfides and chalcophile elements. On average, sulfide grains throughout the layering were composed of pyrrhotite (81 vol.%; Fe1-x S), chalcopyrite (16 vol.%; CuFeS2 ), and pentlandite (3 vol.%; [Ni, Fe, Co]9 S8 ), which reflect paragenesis of magmatic origin. The sulfides were most commonly associated with Fe-Ti oxides (titanomagnetites and ilmenites), amphiboles, and apatites located at the interstitial positions between clinopyroxene, plagioclase, and olivine. Pentlandite exsolution textures in pyrrhotite indicate that the sulfides formed from high-temperature sulfide liquid separated from mafic magma that exsolved upon cooling. The relatively homogenous phase proportion within sulfides along with their chemical and isotopic compositions throughout the studied intervals further support the magmatic origin of sulfide enrichment at the layer boundaries. The studied magmatic layers were likely formed as a result of intrusion of more primitive magma (fine-grained gabbro) into the former crystal mush (coarse-grained gabbro). Sulfides from the coarse-grained gabbros are Ir-Platinum Group Element-rich (PGE; i.e., Ir, Os, Ru) but those from the fine-grained gabbros are Pd-PGE-rich (i.e., Pd, Pt, Rh). Notably, the sulfides from the layer boundaries are also enriched in Pd-PGEs, and therefore elevated sulfide contents at the boundaries were likely related to the new intruding melt. Because S concentration at sulfide saturation level is dependent on the Fe content of the melt, sulfide crystallization may have been caused by FeO loss, both via crystallization of late-precipitating oxides at the boundaries, and by exchange of Fe and Mg between melt and Fe-bearing silicates (olivine and clinopyroxene). The increased precipitation of sulfide grains at the layer boundaries might be widespread in the lower oceanic crust, as also observed in the Semail ophiolite and along the Mid-Atlantic Ridge. Therefore, this process might affect the metal budget of the global lower oceanic crust. We estimate that up to ∼20% of the Cu, ∼8% of the S, and ∼84% of the Pb of the oceanic crust inventory is accumulated at the layer boundaries only from the interaction between crystal mush and new magma.